An effective stacking fault energy viewpoint on the formation of extended defects and their contribution to strain hardening in a Fe–Mn–Si–Al twinning-induced plasticity steel. (March 2015) - Mahato, B.; Shee, S.K.; Sahu, T.; Ghosh Chowdhury, S.; Sahu, P.; Porter, D.A.; Karjalainen, L.P.
Abstract: A deformation-dependent stacking fault energy (SFE) viewpoint is invoked to interpret the low strain rate tensile deformation of a Fe–27Mn–2.5Si–3.5Al austenitic steel at room temperature by using X-ray diffraction analyses and transmission electron microscopy (TEM) observations. The effective SFE of austenite increased with strain from ∼18 to 40 mJ m −2, and it was reasoned that this was the result of the increase in strain energy of the stacking faults (SFs) per unit area due to its dependence on the dislocation character and density. Twinning was observed at 2% strain and confirmed to occur by a glide mechanism of a 6 〈 1 2 1 〉 Shockley partial dislocations, leading to the formation of overlapping intrinsic–extrinsic SF pairs representing a three-layer twin embryo, revealing periodic dislocation contrast in TEM. The early onset of twinning is attributed to the unusually low critical twinning stress of the steel, ∼200 MPa. In spite of twinning, the stacking fault probability ( Psf ) of twinned austenite was remarkably low (∼10 −4 ) at low strains, but increased moderately (to ∼10 −3 ) up to failure strain. At the emergence of twinning, the corresponding perfect dislocation density was low (∼10 14  m −2 ) but was well above the critical dislocation density required for twinning occurrence. Dislocation character analysis indicated that increasing deformation gradually changed the dislocation character from edge to screw type. The microstructural parameters of the steel estimated in direct or indirect relation to its SFE could explain its flow stress and strain hardening behavior.